SISTEM BUKA TUTUP PINTU OTOMATIS BERBASIS SUARA - Ariyanti, Sinta; Adi, Slamet Seno; Purbawanto, Sugeng (Department of Electronic and Informatic Engineering Education, Faculty of Engineering, UNY, 2018)
Biometric identification is one of the media on the operation of the system of home automation are much sought after.This is because conventional identification such as the use of your PIN, password, and a key card is already not enough reliable, in terms of security and how to operate.Biometrics is essentially an introduction to someone based on the unique personality of each person owned such as facial recognition, fingerprints, voice recognition, the introduction of the retina, and signature.Voice recognition is a process to identify a person by recognizing speech from that person.The purpose of this research is to know the success rate of the giving of the commandments on the system open close the door automatically using voice recognition. The methods used in this study is the method waterfall and consist of systems analysis, the design, implementation, and Â testing. This system uses the module Easy VR as an introduction to his voice. Easy device VR 3.0 can be an alternative in the build system-based voice recognition, as have a number of benefits that is its small size, has a user-defined feature speaker dependent, so for its implementation can be minimize the complexity of installation and configuration of the function of the device is relatively simple.This study uses two words used to code the words